Psalm 74: myth as the source of hope in times of devastation - Baumann, Gerlinde (Verbum et ecclesia, 2006)
The reference to mythical traditions in Psalm 74 is not just an allusion to a common set of motifs. It is an essential strategy to gain hope in desperate times, when the country is completely destroyed. The article shows this mainly by working on the structure and the metaphors of the psalm. The authors of Psalm 74 created hope in a hopeless situation by referring to a dimension beyond the visible sphere. The deeds of YHWH/Elohim in the mythical traditions cannot be reached by the enemies: the God-established orders of time and space cannot be destroyed by their violence.